Pengaruh Emotional, Spritual dan Adversity Quotient terhadap Loyalitas Karyawan dalam Organisasi (Studi Kasus di KCU BCA Kedoya Permai Tbk Jakarta) - Firman Fauzi; Gilbert Siagian (Jurnal Ilmiah Poli Bisnis, 2019)
This study aims to analyze the influence of emotional, spiritual and adversity quotient on employee loyalty in the organization. This study used a sample of 85 respondents residing at KCU BCA Kedoya Permai Tbk, Jakarta. The sampling method uses Purposive Sampling. The test model uses SPSS 22.0 version with a validity and reliability test that uses a significance level of 0.05 and a multicollinearity test, a normality test uses the Kolmogorov-Smirnov test. Hypothesis test uses the coefficient of determination test, t sta and F statistical test This study proves that Emotional Quotient, Spiritual Quotient and Adversity Quotient have a positive and significant effect on employee loyalty in the organization. Keywords: Emotional Quotient, Spiritual Quotient, Adversity Quotient and Loyalty in Organizations